THE EFFECTS OF OPERATING CONDITIONS ON THE RELIABILITY OF THE COMPRESSOR MOTORS OF ELECTRIC DIRECT CURRENT - Dubynets, L. V.; Ustymenko, D. V.; Zhernakov, Ye. O.; Krasnov, R. V. (Science and Transport Progress, 2007)
On the basis of the statistical data it is lead, research of influence of conditions of operation on reliability of engines of compressors. A principal cause of failure of engines is significant overheating windings of an anchor and the main poles owing to long overloads a current. One of ways of the decision of this problem is improvement of the equipment of protection.